FRACTAL KINETICS ANALYSIS OF ENZYMATIC HYDROLYSIS OF SAWDUST USING CELLULASE IN ETHANOL PRODUCTION - Megawati, Megawati; Fardhyanti, Dewi Selvia; Prasetiawan, Haniif; Hartanto, Dhoni; Khoiroh, Ianatul; Suwito, Slamet; Kuntoro, Kuntoro (Universitas Negeri Semarang, 2018)
Sawdust is one of the abundantly lignocellulosic materials in the world. Sawdust is considered promosing for ethanol production, because it contains mainly lignin, hemicellulose, and cellulose. The drying process was applied to pretreat sawdust to make its degradation process easier. Biodegradation of sawdust was conducted by enzymatic hydrolysis using cellulase. The volume of cellulase in the hydrolysis substrate was varied from 5 to 9% v/v. The sugar concentration produced by enzymatic hydrolysis of sawdust every 1 h was recorded as well as its fractal kinetics analysis. Fermentation using yeast in 5 days was also performed to convert sugar hydrolysate to ethanol. Optimal sugar concentration in hydrolysate obtained was about 0.15 mol/L with cellulase volume of 9% v/v and its ethanol concentration was about 0.059% v/v. Fractal kinetics models by Kopelman and Valjamae which can quantitatively describe enzymatic hydrolysis of sawdust using cellulase were used. However, the result of this study indicated that, at high enzyme volume (9% v/v), Valjamae model was more suitable than Kopelman. The fractal exponent value (h) was about 0.667 and the rate constants (k) were about 0.44, 0.53, and 0.58 1/h at the enzyme volume of 5, 7, and 9% v/v. Thus, it can be concluded that enzyme volumes significantly effect rate constants.